The Constitutionality of Priority Allocation of Mining Business License Areas in Indonesia: A Perspective on State Control and Equal Opportunity under PP No. 25 of 2024 - Muslim Lobubun (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2024)
Changes in mining policy under Law Number 3 of 2020 introduced a priority mechanism for granting Mining Business License Areas (WIUP) alongside the auction system. This policy raises constitutional issues concerning limitations on equal opportunity principles and potential deviations from the state's right of control. This normative legal research analyzes the legal construction of priority WIUP allocation and evaluates its constitutionality based on the State's Right of Control standards articulated in Constitutional Court Decision Number 36/PUU-X/2012. The findings indicate that granting priority without measurable merit criteria risks reducing the constitutional essence of state control intended for the greatest prosperity of the people. This study formulates constitutional criteria for priority WIUP allocation, comprising legitimate affirmative purposes, technical and financial capacity, transparency, and continuous oversight, ensuring that such preference remains aligned with the principles of fair legal certainty.